How multiculturalism impacts management process within international corporations - MILITARU, Cezar; ZANFIR, Adriana (Annals of Spiru Haret University. Economic Series, 2010)
International business conflicts take place when one part sends a message in accordance with a specific culture, while the other part decodes the message considering another set of values, corresponding to their own culture. This situation is present because the particularities of other cultures are not known. Very often, the fact that people belonging to other cultures are different is ignored, through their religion, statute, decisions they take, attitude towards time and nonverbal language. Therefore, the essential element in taking decisions in the international business environment for the corporations that are involved in a global competition is the adjustment of management methods and techniques into the specific cultural space where they operate.